2019
DOI: 10.1016/j.exer.2019.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Development of lacrimal gland inflammation in the mouse model of herpes stromal keratitis

Abstract: Herpes stromal keratitis (HSK) is a chronic immunoinflammatory condition which develops in response to recurrent herpes simplex virus-1 (HSV-1) infection of the cornea. Patients with HSK often demonstrate the concurrence of corneal desiccation and the loss of blink reflex. However, the relationship between severity of HSK, level of basal tears and inflammation of the lacrimal gland is mostly unexplored. In this study, we compared these variables in extraorbital lacrimal gland (EoLG) after corneal HSV-1 infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In a paper submitted at the time of the submission of the present paper and recently published, another group reported that HSV-1 infected the ELG following corneal infection and that this infection led to a loss in tear production initially noted at day 7 p.i. (47). In addition, glandular pathology associated with CD4 ϩ and CD8 ϩ T cell infiltration and expression of IFN-␥ was described and was correlative to the severity of HSV-1 keratitis.…”
Section: Discussionmentioning
confidence: 96%
“…In a paper submitted at the time of the submission of the present paper and recently published, another group reported that HSV-1 infected the ELG following corneal infection and that this infection led to a loss in tear production initially noted at day 7 p.i. (47). In addition, glandular pathology associated with CD4 ϩ and CD8 ϩ T cell infiltration and expression of IFN-␥ was described and was correlative to the severity of HSV-1 keratitis.…”
Section: Discussionmentioning
confidence: 96%
“…Inflammation is involved in many lacrimal gland diseases, such as high-fat diet–related dry eye, autoimmune disease–related dry eye, and graft-versus-host disease–related dry eye. 32 34 Lacrimal duct blockage–induced inflammation may also contribute to acinar cell apoptosis and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal involvement is usually a precursor for corneal scarring due to the infiltration of inflammation regulatory agents[ 275 ]. Rao et al [ 276 ] in their study showed the development of lacrimal gland inflammation in a mouse model of herpes stromal keratitis underpinning the inflammatory origin of herpes stromal keratitis[ 276 ]. Ocular infestation of the HSV is usually secondary to an infection in another part of the body[ 277 ].…”
Section: Complications Of Herpes Simplex Keratitis: Corneal Scarring ...mentioning
confidence: 99%